Reliability and validity of Turkish versions of sciatica bothersomeness and sciatica frequency index - SAÇAKLIDIR, REKİB; GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (My University, 2022)
BACKGROUND: The Sciatica Frequency Index (SFI) and Sciatica Bothersomeness Index (SBI) are two separate indices scored for both the bothersomeness and frequency of radiating symptoms. There is no Turkish scale used specifically for sciatica.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); REHABİLİTASYON; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); REHABILITATION; Ayak Bakımı; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Ortopedi ve Spor Hekimliği; Podiatry; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Orthopedics and Sports Medicine; Lumbar region; sciatica; reliability and validity; CROSS-CULTURAL ADAPTATION; LOW-BACK-PAIN; DISABILITY INDEX; HEALTH; VALIDATION; QUESTIONNAIRE; MANAGEMENT; HERNIATION; OUTCOMES; SURGERY